2016
DOI: 10.4236/ojn.2016.610086
|View full text |Cite
|
Sign up to set email alerts
|

Managing the Needs of Older Patients with Multimorbidity—A Systematic Review of the Challenges Faced by the Healthcare Services

Abstract: Research fails to provide an overview of the challenges involved in caring for older patients with multimorbidity. Multimorbidity is defined as the presence of two or more chronic conditions in the same person, leading to a high risk of care dependency. The aim of this review was to illuminate the challenges faced by the healthcare services in managing the needs of older patients with multimorbidity. A systematic review was performed, a total of 1,965 abstracts were read and nine quantitative studies included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
(156 reference statements)
0
5
0
Order By: Relevance
“…With the increase in the SDI, the stable trend of a lower mortality rate of thyroid cancer may be due to the overall 10-year survival rate for most treatable types of thyroid cancer, at 92–98%, except for incurable types such as anaplastic thyroid carcinoma ( 27 ). We also found that thyroid cancer-related mortality increased with increasing age, which may be due to the poor prognosis of thyroid cancer in elderly individuals because of their weakened immune system and underlying diseases ( 28 , 29 ). Other explanations may be the rapid population aging process and lack of professional medical staff in China.…”
Section: Discussionmentioning
confidence: 72%
“…With the increase in the SDI, the stable trend of a lower mortality rate of thyroid cancer may be due to the overall 10-year survival rate for most treatable types of thyroid cancer, at 92–98%, except for incurable types such as anaplastic thyroid carcinoma ( 27 ). We also found that thyroid cancer-related mortality increased with increasing age, which may be due to the poor prognosis of thyroid cancer in elderly individuals because of their weakened immune system and underlying diseases ( 28 , 29 ). Other explanations may be the rapid population aging process and lack of professional medical staff in China.…”
Section: Discussionmentioning
confidence: 72%
“…One possible cause may have been the poorer prognosis of TC in older age groups because of their weakened immune system, multimorbidity, and higher allcause mortality. 49,50 Another explanation for the lower QOC in older people could have been the rapid population aging process and paucity of informed and skilled caregivers in most countries. 51 Moreover, overall better care was seen in favor of women in higher SDI regions, whereas men received better care in lower SDI regions.…”
Section: Discussionmentioning
confidence: 99%
“…The inspection of TC QCI in various age groups revealed an overall higher QOC in younger adults, while older people received lower QOC. One possible cause may have been the poorer prognosis of TC in older age groups because of their weakened immune system, multimorbidity, and higher all‐cause mortality 49,50 . Another explanation for the lower QOC in older people could have been the rapid population aging process and paucity of informed and skilled caregivers in most countries 51 …”
Section: Discussionmentioning
confidence: 99%
“…Scarce resources, cross-pressure and value conflicts increase the risk of missed care, moral stress, sick leave and the number of nurses who want to leave the profession (Indregard et al, 2018; Kristiansen et al, 2015; Morley et al, 2020; Tønnessen et al, 2020). Long-term care is typically characterized by long-lasting and close relationships between nurses and patients (McCormack et al, 2017), few colleagues to consult with (Lillemoen & Pedersen, 2013) and concerns about care quality and capacity (Botngård et al, 2021; Holm et al, 2016). Therefore, it is especially important to examine nurses' experience with and handling of daily ethical challenges in this context.…”
Section: Introductionmentioning
confidence: 99%